Global Mild Solutions and Attractors for Stochastic Viscous Cahn-Hilliard Equation - Xuewei Ju; Hongli Wang; Desheng Li; Jinqiao Duan (Abstract and Applied Analysis)
This paper is devoted to the study of mild solutions for the initial and boundary value problem of stochastic viscous Cahn-Hilliard equation driven by white noise. Under reasonable assumptions we first prove the existence and uniqueness result. Then, we show that the existence of a stochastic global attractor which pullback attracts each bounded set in appropriate phase spaces.